Emperor Hirohito - Robinson, Tim; BBC Discovery Channel ([New South Wales, Australia] : BBC Active, 2005)
At the end of World War II Japan was under American control. The trial for war crimes of Emperor Hirohito was widely anticipated. It never took place. This documentary outlines the amazing story of how American prosecutors and Japanese elite circles ensured the Emperor was not put on trial.
Editor, John Farren.
Narrated by Michael Praed.
DVD format.
Keywords: Hirohito, -- Emperor of Japan, -- 1901-1989.; Japan -- History -- 1945-.